The Effectiveness Rate of Products Before and After the Use of E-Billing Method - Sahade, Sahade; Adi, Adi (Budapest International Research and Critics University, 2021)
This study aims at finding out the use of e-billing method in increasing the effectiveness of the realization of tax payable as stated in the the Tax Service Office of Makassar Utara. The variables in this research are the independent variables of the receiver as the independent variables and billing as the dependent variables. The population of this research is the realization of tax payable occurring in the Tax Service Office of Makassar Utara. The sample in this research is the realization of the receipts of the year 2011 to the year 2016. The data collection techniques used was documentation. The data analysis technique used is the effectiveness. The result of the research show that: (1) the effectiveness of Tax payable in Tax Service Pratama Office Makassar Utara before the application of e-billing system in 2011 amounted to 97%, the year of 2012 was 88,29% and 68,93% in 2013. (2) the effectiveness of tax payable in the first year of e-billing implementation in 2014 which was 102%, 94% in 2015 and 97% in 2016. The average rate of tax payable effectiveness before the use of e-billing was 88.74% and the tax payable effectiveness rate after the application of e-billing was 97,6%. This shows that the use of e-billing system has been able to improve the effectiveness of tax revenue in Tax Service Pratama Office Makassar Utara. Hence, the hypotheses proposed in the study are accepted.